THU0420 Long-Term (104-Week) Efficacy and Safety Profile of Apremilast, An Oral Phosphodiesterase 4 Inhibitor, in Patients with Psoriatic Arthritis: Results from a Phase III, Randomised, Controlled Trial and Open-Label Extension (Palace 1). (9th June 2015) - Kavanaugh, A.; Adebajo, A.; Gladman, D.; Gomez-Reino, J.; Hall, S.; Lespessailles, E.; Mease, P.; Schett, G.; Shah, K.; Hu, C.; Wollenhaupt, J.
Abstract : Background: Apremilast (APR), an oral phosphodiesterase 4 inhibitor, helps regulate immune responses in psoriatic arthritis (PsA). PALACE 1 compared the efficacy and safety of APR with placebo (PBO) in patients with active PsA despite prior conventional disease-modifying antirheumatic drugs (DMARDs) and/or biologics. Objectives: Evaluate the efficacy and safety of APR treatment over 104 weeks. Methods: Patients were randomized (1:1:1) to PBO, APR 20 mg BID (APR20), or APR 30 mg BID (APR30) stratified by baseline DMARD use (yes/no). Patients whose swollen/tender joint counts (SJC/TJC) had not improved ≥20% at Week 16 were considered non-responders and were required to be re-randomized (1:1) to APR20 or APR30 if they were initially randomized to PBO, or continued on their initial APR dose. At Week 24, all remaining PBO patients were re-randomized to APR20 or APR30. Double-blind APR treatment continued to Week 52; patients could continue APR for up to 4 additional years. Results: 504 randomized patients received ≥1 dose of study medication (PBO: n=168; APR20: n=168; APR30: n=168). At Week 52, 53.2% of patients receiving APR30 and 59.6% of patients receiving APR20 achieved a modified ACR20 response (Table ); ≈ 80% (285/344) of patients completing Week 52 were still receiving APR at the data cutoff during their second year of APR exposure. Patients taking APR demonstrated sustained improvements at Week 104 as shown by modified ACR20/ACR50/ACR70 response rates, SJC/TJC mean percent change, HAQ-DI mean change, proportion of patients with HAQ-DI exceeding the minimal clinically important difference (MCID) ≥0.30 threshold, mean change in DAS-28 (CRP), achievement of DAS (CRP) <2.6, and PASI-50/PASI-75 responses (Table ). No new safety concerns were identified with treatment through Week 104. During Weeks >52 to ≤104, adverse events (AEs) occurring in ≥5% of APR-exposed patients were nasopharyngitis and upper respiratory tract infection; most AEs were mild/moderate in severity. Diarrhea (1.7%) and nausea (1.2%) occurred at lower rates in Weeks >52 to ≤104 than in Weeks 0 to ≤52 (15.3% and 12.4%, respectively). Serious AEs occurred in 4.7% (APR30) and 6.4% (APR20) of patients over Weeks >52 to ≤104. Fewer discontinuations due to AEs occurred during Weeks >52 to ≤104 (1.5%) vs. Weeks 0 to ≤52 (8.2%). Conclusions: Over 104 weeks, APR demonstrated sustained clinically meaningful improvements in signs and symptoms of PsA, including physical function, and associated psoriasis. APR continued to demonstrate an acceptable safety profile and was generally well tolerated. Disclosure of Interest: A. Kavanaugh Grant/research support from: Abbott, Amgen, Astra-Zeneca, Bristol-Myers Squibb, Celgene Corporation, Centocor-Janssen, Pfizer Inc, Roche, and UCB, A. Adebajo: None declared, D. Gladman Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Celgene Corporation, Janssen, Pfizer Inc, Novartis, and UCB, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene Corporation, Janssen, Pfizer Inc, Novartis, and UCB, J. Gomez-Reino Grant/research support from: Roche and Schering-Plough, Consultant for: Bristol-Myers Squibb, Pfizer Inc, Roche, Schering-Plough, and UCB SA, Speakers bureau: Bristol-Myers Squibb, Roche, Schering-Plough, and Wyeth; S. Hall Consultant for: Amgen, AstraZeneca, Boehringer Ingelheim, Centocor, GlaxoSmithKline, MSD, Pfizer, Sanofi Aventis, Sanofi Pasteur, Schering-Plough, Serono, and Wyeth; Paid instructor for: Boehringer Ingelheim, MSD, Roche Schering Plough, Servier, and Wyeth., Speakers bureau: Boehringer Ingelheim, GlaxoSmithKline, MSD, Pfizer, Roche, Sanofi Aventis, Schering-Plough, and Wyeth, E. Lespessailles Grant/research support from: Amgen, Eli Lilly, Novartis, and Servier, Speakers bureau: Amgen, Eli Lilly, Novartis, and Servier, P. Mease Grant/research support from: Abbott, Amgen, Biogen Idec, Bristol-Myers Squibb, Genentech, Janssen, Eli Lilly, Pfizer Inc, UCB, Celgene Corporation, Novartis, and Roche, Consultant for: Abbott, Amgen, Biogen Idec, Bristol-Myers Squibb, Genentech, Janssen, Eli Lilly, Pfizer Inc, UCB, Celgene Corporation, Novartis, and Roche, Speakers bureau: Abbott, Amgen, Biogen Idec, Bristol-Myers Squibb, Genentech, Janssen, Eli Lilly, Pfizer Inc, UCB, G. Schett Grant/research support from: Abbott, Celgene Corporation, Roche, and UCB, Consultant for: Abbott, Celgene Corporation, Roche, and UCB, K. Shah Employee of: Celgene Corporation, C. Hu Employee of: Celgene Corporation, J. Wollenhaupt Grant/research support from: Abbott, Bristol-Myers Squibb, MSD, Pfizer Inc, and UCB, Consultant for: Abbott, Bristol-Myers Squibb, MSD, Pfizer Inc, and UCB